Improving immunization capacity in Ethiopia through continuous quality improvement interventions: a prospective quasi-experimental study - Tsegahun Manyazewal; Alemayehu Mekonnen; Tesfa Demelew; Semegnew Mengestu; Yusuf Abdu; Dereje Mammo; Workeabeba Abebe; Belay Haffa; Daniel Zenebe; Bogale Worku; Amir Aman; Setegn Tigabu (BMC, 2018)
Abstract Background Strong scientific evidence is needed to support low-income countries in building effective and sustainable immunization programs and proactively engaging in global vaccine development and implementation initiatives. This study aimed to implement and evaluate the effectiveness of system-wide continuous quality improvement (CQI) interventions to improve national immunization programme performance in Ethiopia. Methods The study used a prospective, quasi-experimental design with an interrupted time-series analysis to collect data from 781 government health sectors (556 healthcare facilities, 196 district health offices, and 29 zonal health departments) selected from developing and emerging regions in Ethiopia. Procedures included baseline quality assessment of immunization programme and services using structured checklists; immunization systems strengthening using onsite technical support, training, and supportive supervision interventions in a Plan-Do-Check-Act cycle over 12 months; and collection and analysis of data at baseline and at the 6th and 12th month of interventions using statistical process control and the t-test. Outcome measures were the coverage of the vaccines pentavalent 3, measles, Bacillus Calmette-Guérin vaccine (BCG), Pneumococcal Conjugate Vaccine (PCV), as well as full vaccination status; while process measures were changes in human resources, planning, service delivery, logistics and supply, documentation, coordination and collaboration, and monitoring and evaluation. Analysis and interpretation of data adhered to SQUIRE 2.0 guidelines. Results Prior to the interventions, vaccination coverage was low and all seven process indicators had an aggregate score of below 50%, with significant differences in performance at healthcare facility level between developing and emerging regions (P = 0.0001). Following the interventions, vaccination coverage improved significantly from 63.6% at baseline to 79.3% for pentavalent (P = 0.0001), 62.5 to 72.8% for measles (P = 0.009), 62.4 to 73.5% for BCG (P = 0.0001), 65.3 to 81.0% for PCV (P = 0.02), and insignificantly from 56.2 to 74.2% for full vaccination. All seven process indicators scored above 75% in all regions, with no significant differences found in performance between developing and emerging regions. Conclusions The CQI interventions improved immunization capacity and vaccination coverage in Ethiopia, where the unstable transmission patterns and intensity of infectious diseases necessitate for a state of readiness of the health system at all times. The approach was found to empower zone, district, and facility-level health sectors to exercise accountability and share ownership of immunization outcomes. While universal approaches can improve routine immunization, local innovative interventions that target local problems and dynamics are also necessary to achieve optimal coverage.